2004
DOI: 10.1353/asi.2004.0018
|View full text |Cite
|
Sign up to set email alerts
|

Hominid Dispersals and Asian Biogeography during the Lower and Early Middle Pleistocene, c. 2.0-0.5 Mya

Abstract: This paper examines the environmental context of human dispersals into Asia up to 0.5 mya. These dispersals were probably intermittent, often discontinuous, and initially confined to warm grasslands and open woodlands across southern Asia. During the Early Pleistocene, the effects of the uplift of Tibet and the inception of the monsoon were muted by the low-amplitude nature of northern hemisphere glaciations. By the Middle Pleistocene, further uplift, stronger monsoonal circulation, and higher-amplitude, glaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 85 publications
0
24
0
4
Order By: Relevance
“…In Asia, Dennell (2004) and Dennell et al (2011) suggests that dispersal were probably intermittent, often discontinuous. Initially colonisation was confined to warm grasslands and open woodlands across southern Asia following the same climate and vegetation latitudinal band from the west to the east.…”
Section: Consequences For Dispersalmentioning
confidence: 99%
“…In Asia, Dennell (2004) and Dennell et al (2011) suggests that dispersal were probably intermittent, often discontinuous. Initially colonisation was confined to warm grasslands and open woodlands across southern Asia following the same climate and vegetation latitudinal band from the west to the east.…”
Section: Consequences For Dispersalmentioning
confidence: 99%
“…The oldest material of all, dating from the early part of the Early Pleistocene, is found in southeast Europe, presumably reflecting the initial migration of early humans from Africa into Europe via the Levant, tracking structurally familiar biomes (e.g. Dennell, 2004). Key sites of great antiquity (Fig.…”
Section: Rivers Wipper and Ilmmentioning
confidence: 99%
“…It has been 33 suggested that the expansion of savanna environments during the Early Pleistocene 34 allowed for the first 'Out of Africa I' dispersal (Dennell, 2004;Martínez-Navarro, 2004) 35 and that humans dispersed into Western Europe during warmer periods and that the 36 dispersal was highly influenced by climate rather than culture, which played only a minor 37 role (Agustí et al, 2009a). However, these theories assume as a working hypotheses that 38 the presence of hominins and faunal present in the paleontological and archaeological 39 record is continuous.…”
Section: Introduction 30mentioning
confidence: 99%